Bacteriophage endolysins as novel antimicrobials. (October 2012) - Schmelcher, Mathias; Donovan, David M; Loessner, Martin J
Endolysins are enzymes used by bacteriophages at the end of their replication cycle to degrade the peptidoglycan of the bacterial host from within, resulting in cell lysis and release of progeny virions. Due to the absence of an outer membrane in the Gram-positive bacterial cell wall, endolysins can access the peptidoglycan and destroy these organisms when applied externally, making them interesting antimicrobial candidates, particularly in light of increasing bacterial drug resistance. This article reviews the modular structure of these enzymes, in which cell wall binding and catalytic functions are separated, as well as their mechanism of action, lytic activity and potential as antimicrobials. It particularly focuses on molecular engineering as a means of optimizing endolysins for specific applications, highlights new developments that may render these proteins active against Gram-negative and intracellular pathogens and summarizes the most recent applications of endolysins in the fields of medicine, food safety, agriculture and biotechnology.